The variational iterated method for solving 2D integral equations - Abeer A.A. Aladhab (University of Thi-Qar Journal, 2019)
The main objective of this paper is to study the exact solution and approximate solution type of 2D integral equations, by using the variational iteration method, as well as, giving some illustrative examples of linear and nonlinear equations .We tabulate the exact and approximate results